Dynamic analysis of the non-linear behavior of an ocean buoy for energy harvesting - Ribeiro, Mauricio A.; Tusset, Angelo M.; Lenz, Wagner B.; Balthazar, Jose M. [UNESP] (Springer Nature, 2021)
We investigated the nonlinear dynamic behavior of the system for energy harvesting using ocean wave motion. The system consists of a linear electromagnetic system coupled to a float to move with ocean waves. We define the mathematical modeling of a structure together with the parameters for energy harvesting. In this way, we analyzed average power for the parameters linked to the wave profile, the resistance load of the electromechanical motor, and the nonlinear parameters of spring cubic. Therefore, we also analyze the nonlinear dynamic behavior with Maximum Lyapunov exponent, bifurcation diagrams, phase portraits, and Poincaré maps.